Acceptability of screening for mental health difficulties in primary schools: a survey of UK parents - Emma Soneson; Jasmine Childs-Fegredo; Joanna K. Anderson; Jan Stochl; Mina Fazel; Tamsin Ford; Ayla Humphrey; Peter B. Jones; Emma Howarth (BMC, 2018)
Abstract Background Many children and young people experiencing mental health difficulties (MHD) do not access care, often due to inadequate identification. Schools have a unique potential to improve early identification; however, evidence is limited regarding the acceptability of school-based identification programmes. This study aimed to examine parents' beliefs about the acceptability of school-wide MHD screening in primary schools. Methods We collaborated with experts in school-based mental health to develop a questionnaire to measure parental attitudes toward school-wide MHD screening. The questionnaire contained 13 items relating to acceptability; three open-text boxes for comments on harms, benefits, and screening in general; and four questions that captured demographic information. Parents of children attending four primary schools in Cambridgeshire and Norfolk completed the questionnaire. We calculated counts, percentages, and means for each statement, and analysed responses to open-ended questions using content analysis. Results Two hundred ninety parents returned the questionnaire across the four schools (61% response rate). In the 260 questionnaires analysed, a total of 254 parents (98%) believed that it is important to identify MHD early in life, and 251 (97%) believed that schools have an important role in promoting pupils' emotional health. The majority of parents (N = 213; 82%) thought that screening would be helpful, although 34 parents (13%) thought that screening would be harmful. Perceived harms of screening included inaccurate identification, stigmatisation, and low availability of follow-up care. There was no clear consensus regarding how to obtain consent or provide feedback of screening results. There were no significant differences in responses according to ethnicity, gender, age, or school. Conclusions Results suggest that most parents within the socio-demographic context of our study will accept MHD screening within primary schools, and that school-based screening is viable from the perspective of parents. The comments provided about potential harms as well as suggestions for programme delivery are relevant to inform the development and evaluation of acceptable and sustainable school-based identification models. Implementation and scale-up of such programmes will require further understanding of the perspectives of mental health professionals, school staff, and the general public as well as further evaluation against the established standards for identification programmes.